The Effect of Natural Mineral Water on Regulators of Gastroduodenal Motility in Young Adults: a Comparative Controlled Study - Aleksey Е. Shklyaev; Daniil D. Kazarin; Kirill V. Maksimov (Вестник восстановительной медицины)
INTRODUCTION. Drinking balneotherapy has long been successfully used for pathologies of the digestive system. However, the sanogenetic mechanisms of normalization of gastrointestinal motility when using drinking mineral waters have not been sufficiently studied.